Silver Compositing Boosts Water Electrolysis Activity and Durability of RuO2 in a Proton-Exchange-Membrane Water Electrolyzer - Tang, Jiayi; Zhong, Y.; Su, Chao; Shao, Zongping (2023)
Proton-exchange-membrane water electrolyzers (PEMWEs) are of particular interest for green hydrogen production, where the oxygen evolution reaction (OER) at the anode largely determines the overall efficiency. Up to now, only ultrafine IrO2 catalyst gives desirable performance, while its scarcity and high cost inhibit the widespread application. RuO2 catalyst is the most promising alternative, while its practical application is greatly hindered by poor durability. Herein, the greatly boosted performance of conventional sub-micrometer RuO2 by compositing with Ag is reported, and both the morphology of Ag and the compositing way significantly affect the electrolysis performance. The PEMWE fabricated with a two-layer RuO2/Ag nanowire (NWs) composite anode achieves 1.77 A cm−2 at 2.00 V, due to a prominent 44.6 times increase of the electronic conductivity, which greatly improves the catalyst utilization. In addition, mass transportation at high-current-density region is enhanced due to the highly porous feature of Ag NW layer. Long-term stability under high current density of 1 A cm−2 for 100 h is proved with the composite anode, due to the suppressed degradation of RuO2 by silver compositing. This work may accelerate the widespread commercialization of PEMWEs by providing a new way for developing IrO2-free anode.